High Speed AFM and NanoInfrared Spectroscopy Investigation of Aβ1–42 Peptide Variants and Their Interaction With POPC/SM/Chol/GM1 Model Membranes - Feuillie, Cecile; Lambert, Eleonore; Ewald, Maxime; Azouz, Mehdi; Henry, Sarah; Marsaudon, Sophie; Cullin, Christophe; Lecomte, Sophie; Molinari, Michael (Frontiers in Molecular Biosciences, 2020)
Due to an aging population, neurodegenerative diseases such as Alzheimer’s disease (AD) have become a major health issue. In the case of AD, Aβ1–42 peptides have been identified as one of the markers of the disease with the formation of senile plaques via their aggregation, and could play a role in memory impairment and other tragic syndromes associated with the disease. Many studies have shown that not only the morphology and structure of Aβ1–42 peptide assembly are playing an important role in the formation of amyloid plaques, but also the interactions between Aβ1–42 and the cellular membrane are crucial regarding the aggregation processes and toxicity of the amyloid peptides. Despite the increasing amount of information on AD associated amyloids and their toxicity, the molecular mechanisms involved still remain unclear and require in-depth investigation at the local scale to clearly decipher the role of the sequence of the amyloid peptides, of their secondary structures, of their oligomeric states, and of their interactions with lipid membranes. In this original study, through the use of Atomic Force Microscopy (AFM) related-techniques, high-speed AFM and nanoInfrared AFM, we tried to unravel at the nanoscale the link between aggregation state, structure and interaction with membranes in the amyloid/membrane interaction. Using three mutants of Aβ peptides, L34T, oG37C, and WT Aβ1–42 peptides, with differences in morphology, structure and assembly process, as well as model lipidic membranes whose composition and structure allow interactions with the peptides, our AFM study coupling high spatial and temporal resolution and nanoscale structure information clearly evidences a local correlation between the secondary structure of the peptides, their fibrillization kinetics and their interactions with model membranes. Membrane disruption is associated to small transient oligomeric entities in the early stages of aggregation that strongly interact with the membrane, and present an antiparallel β-sheet secondary structure. The strong effect on membrane integrity that exists when these oligomeric Aβ1–42 peptides interact with membranes of a particular composition could be a lead for therapeutic studies.